Association of body mass index and its classifications with gray matter volume in individuals with a wide range of body mass index group: A whole-brain magnetic resonance imaging study - Hidese, Shinsuke; Ota, Miho; Matsuo, Junko; Ishida, Ikki; Yokota, Yuuki; Hattori, Kotaro; Yomogida, Yukihito; Kunugi, Hiroshi (Frontiers in Human Neuroscience, 2022)
Aim: To examine the association of body mass index (BMI) [kg/m2] and its classifications (underweight, normal, overweight, and obese) with brain structure in individuals with a wide range of BMI group. Methods: The participants included 382 right-handed individuals (mean age: 46.9 ± 14.3 years, 142 men and 240 women). The intelligence quotient was assessed using the Japanese Adult Reading Test. Voxel-based morphometry (VBM) and diffusion tensor imaging (DTI) were performed to analyze the association between BMI and gray and white matter structures, respectively. Results: According to VBM, BMI was significantly and negatively correlated with regional gray matter volumes in the bilateral cerebellum exterior. In group comparisons, regional gray matter volume in the right cerebellum exterior was significantly lower in the overweight or obese group than in the underweight or normal group, while that in the bilateral cuneus and calcarine cortex, left cuneus, and left precuneus was significantly lower in the underweight group than in the non-underweight group. Sex-related stratification analyses for VBM revealed that BMI was significantly and negatively correlated with the bilateral cerebellum exterior volumes only in women. In group comparisons, regional gray matter volume in the left cerebellum exterior was significantly lower in obese women than in non-obese women. Regional gray matter volumes in the left thalamus proper and the right cerebellum exterior were significantly lower in overweight or obese group than in underweight or normal group in men and women, respectively. Regional gray matter volume in the bilateral cuneus and calcarine cortex, left cuneus and calcarine cortex, and bilateral cuneus was significantly lower in underweight men than in non-underweight men. In contrast, there were no notable findings on DTI. Conclusion: Our results suggest association of continuous BMI, being overweight or obese, and being underweight with decreased gray matter volume in individuals with a wide range of BMI group. Furthermore, sex-related differences are seen in the association of BMI and its classifications with regional gray matter volume reductions. Abnormally high or low BMIs may have a negative influence on regional gray matter volumes.